Analisis Faktor - Faktor Yang Mempengaruhi Preferensi Konsumen Dalam Pembelian Produk Frozen Food (Studi Kasus Pelanggan “Nadelia Frozen” Patumbak Medan) - Rivaldi Pranata; Rahmayati Rahmayati (STIKes Ibnu Sina Ajibarang, 2023)
Frozen food is food that is processed and then packaged in half-cooked packaging and when consumed must go through a re-processing process, namely by heating it in a frying pan. Frozen Food is a storage process before processing. Frozen food or processed frozen food is the result of a food preservation method which is carried out by lowering the temperature to freezing point, this aims to slow down the spoilage process and preserve the food for months depending on the type of food. Frozen food is also defined as food that is frozen with the aim of preserving the food until it is ready to be eaten. This research design uses quantitative research methods, which test certain theories by examining the relationships between variables. These variables are measured using research instruments, so that data consisting of numbers can be analyzed based on statistical procedures. This type of research uses associative research. Associative research is a temporary answer to associative problem formulations, namely those that ask about the relationship between two or more variables. In this research, we analyze the influence of price and promotion on consumer preferences at the